2016
DOI: 10.1109/tmech.2016.2603601
|View full text |Cite
|
Sign up to set email alerts
|

Directional Singularity-Robust Torque Control for Gyroscopic Actuators

Abstract: Abstract-Gyroscopic actuation is appealing for wearable applications due to its ability to impart free moments on a body without exoskeletal structures on the joints. We recently proposed an unobtrusive balancing aid consisting of multiple parallelmounted control moment gyroscopes (CMGs) contained within a backpack-like orthopedic corset. Using conventional CMG control techniques, geometric singularities result in a number of performance issues, including either unintended oscillations or freezing of the gimba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…We also propose the quantity of gimbal potential, to characterize the future ability to produce the reference moment, according to the alignment of each gimbal frame with respect to the reference direction. This generalizes and formalizes our previous method, where Berry et al outlined a control method for a collinear configuration of two gimbals [20].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We also propose the quantity of gimbal potential, to characterize the future ability to produce the reference moment, according to the alignment of each gimbal frame with respect to the reference direction. This generalizes and formalizes our previous method, where Berry et al outlined a control method for a collinear configuration of two gimbals [20].…”
Section: Introductionsupporting
confidence: 70%
“…The orthogonality index presented by Oh and Vadali [22] used in our previous study [20] also identified reference-aligned singularities (δ track = 0), but it did not unambiguously identify configurations that allowed good reference tracking (δ track = 1), making it less effective for the design of a steering law.…”
Section: Reference-aligned Singularitiesmentioning
confidence: 82%
“…Finally, arguments also exist for the suitability of certain types of controllers for this particular actuation concept. Due to a finite ability to exchange angular momentum (limited by geometric saturation), gyroscopic actuators are physically incapable of sustaining indefinite or prolonged support to overcome persistent postural bias 85 , but are rather better suited to providing dynamic assistance in response to rapid, transient motions, in which the angular momentum exchange is not monotonic but ideally varying over time such that the net exchange is small. Nevertheless, a posture-dependent controller could, in theory, be adapted to mitigate low-frequent biases, but the behaviour and perception of such a controller has not yet been studied.…”
Section: Subjects Interact Better With Predictable Controllersmentioning
confidence: 99%
“…In aerospace and astronautic engineering, the gyroscopic effect is used in attitude guidance systems for spacecraft and satellites [2,3]. Lemus and Berry [4,5] applied it to develop a balance assistance device for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jin et al [23] used an inverted pendulum to evaluate the efficiency of a stabilizing device before applying it to a bicycle. In studies to enhance human balance using gyroscopic effect, Lemus et al [4,5] conducted experiments on an inverted pendulum test bench instead of using an actual human.…”
Section: Introductionmentioning
confidence: 99%